Performa Sapi Peranakan Ongole Betina yang Diberi Ransum Berbasis Jerami Padi Fermentasi yang Mengandung Indigofera zollingeriana - Asep Suherman; Yudhi Mahmud; Entus Hikmana; Iman Hernaman; Wiwik Ambarsari; Hani Yuhani; Rukmantoro Salim; Asep Suherman (Universitas Sebelas Maret (UNS), 2018)
This reaserch was aimed to study about performance offemale Peranakan Ongole cattle that fed diet based on fermented straw and contains Indigofera zollingeriana. Sixteen offemale PO cattles which were allocated in 4 treatment diets consisting of :R1 = Fermented rice straw A (ad libitum) + 3 kg rice bran, R2= Fermented rice straw A (ad libitum) + 3 kg concentrate, R3= Fermented rice straw A (ad libitum) + 2 kg rice bran + 1 kg Indigofera zollingeriana, R4= Fermented rice straw B (ad libitum) + 2 kg rice bran + 1 kg Indigofera zollingeriana. The experimental used completed randomized design. One-way ANOVA and Ducan’s Multiple Range Testwere performed to compare the significant difference. The T3 and T4 diets containing Indigofera zollingeriana resulted in higher growth gain andaverage daily gain with a lower feed conversion (P <0.05) than the non-Indigofera zollingeriana (T1 and T2) diets. Fermentation of rice straw using rice bran, molasses, and EM-4 used in T4 diet resulted in the highest growth gain and average daily gain (P<0.05) and the lowest feed conversion (P <0.05) i.e. 88.00 kg, 0.807 kg/head/day and 11.2 respectively. Conclusion, the female PO cattles fed diet containing fermented rice straw by rice bran, molasses, and EM-4 (fermented rice straw B)(ad libitum) and 2 kg of rice bran and Indigofera zollingeriana 1 kg (asfed) produces the best performance.